COMPETITIVENESS AS A MULTILEVEL ECONOMIC CATEGORY: ENTERPRISE – INDUSTRY – NATIONAL ECONOMY - SVYNOUS, Ivan; NYKONENKO, Oksana (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article provides a comprehensive study of competitiveness as a multilevel economic category that integrates three interrelated levels – enterprise, industry, and national economy. It emphasizes that competitiveness is not a static property of an economic system but a dynamic process that reflects the ability of various economic actors to create, maintain, and enhance competitive advantages in a rapidly changing global environment. The research substantiates that competitiveness arises from the systemic interaction of micro-, meso-, and macroeconomic processes, where the efficiency of enterprises determines the sectoral potential, while the aggregate performance of industries defines the competitive position of a nation within the global economic space. At the micro level, competitiveness is viewed through the prism of an enterprise’s ability to efficiently use resources, introduce innovations, adapt to market fluctuations, and ensure long-term profitability. At the meso level, it manifests through the effectiveness of inter-firm cooperation, cluster development, investment attractiveness, and technological modernization within industries. The macro level reflects the institutional, infrastructural, and political factors that determine the overall capacity of a national economy to ensure sustainable growth and integration into the global market system. The article identifies and classifies the key determinants of competitiveness — innovation, resource efficiency, digitalization, institutional quality, human capital development, and stability of economic policy. Theoretical approaches to the understanding of competitiveness proposed by A. Smith, D. Ricardo, J. Schumpeter, M. Porter, D. North, and C. Freeman are analyzed and compared with modern Ukrainian interpretations that take into account the transformational specifics of the national economy. The author emphasizes that competitiveness should be studied as a synergistic system where the effectiveness of enterprises, the coherence of industry networks, and the institutional quality of state governance mutually reinforce one another. A systemic approach to assessing competitiveness is proposed, combining classical economic theory with the principles of strategic management, innovation economics, and institutional development. It involves the alignment of enterprise strategies, sectoral cooperation mechanisms, and national reforms aimed at improving the business environment, investment climate, and digital infrastructure. The study concludes that for Ukraine, particularly in the context of post-war recovery and European integration, the formation of an institutional and innovation-based model of development is a strategic priority. Such a model should ensure effective interaction between business, science, and government; strengthen the competitiveness of enterprises and industries; enhance national productivity; and promote sustainable, inclusive, and innovation-driven economic growth in the long term.